Effective Organs-at-Risk Dose Sparing in Volumetric Modulated Arc Therapy Using a Half-Beam Technique in Whole Pelvic Irradiation - Jang, Hyunsoo; Park, Jiyeon; Artz, Mark; Zhang, Yawei; Ricci, Jacob C.; Huh, Soon; Johnson, Perry B.; Kim, Mi-Hwa; Chun, Mison; Oh, Young-Taek; Noh, O Kyu; Park, Hae-Jin (Frontiers in Oncology, 2021)
Background: Although there are some controversies regarding whole pelvic radiation therapy (WPRT) due to its gastrointestinal and hematologic toxicities, it is considered for patients with gynecological, rectal, and prostate cancer. To effectively spare organs-at-risk (OAR) doses using multi-leaf collimator (MLC)’s optimal segments, potential dosimetric benefits in volumetric modulated arc therapy (VMAT) using a half-beam technique (HF) were investigated for WPRT. Methods: While the size of a fully opened field (FF) was decided to entirely include a planning target volume in all beam’s eye view across arc angles, the HF was designed to use half the FF from the isocenter for dose optimization. The left or the right half of the FF was alternatively opened in VMAT-HF using a pair of arcs rotating clockwise and counterclockwise. Dosimetric benefits of VMAT-HF, presented with dose conformity, homogeneity, and dose-volume parameters in terms of modulation complex score, were compared to VMAT optimized using the FF (VMAT-FF). Consequent normal tissue complication probability (NTCP) by reducing the irradiated volumes was evaluated as well as dose-volume parameters with statistical analysis for OAR. Moreover, beam-on time and MLC position precision were analyzed with log files to assess plan deliverability and clinical applicability of VMAT-HF as compared to VMAT-FF. Results: While VMAT-HF used 60%–70% less intensity modulation complexity than VMAT-FF, it showed superior dose conformity. The small intestine and colon in VMAT-HF showed a noticeable reduction in the irradiated volumes of up to 35% and 15%, respectively, at an intermediate dose of 20–45 Gy. The small intestine showed statistically significant dose sparing at the volumes that received a dose from 15 to 45 Gy. Such a dose reduction for the small intestine and colon in VMAT-HF presented a significant NTCP reduction than VMAT-FF. Without sacrificing the beam delivery efficiency, VMAT-HF achieved effective OAR dose reduction in dose-volume histograms. Conclusions: VMAT-HF led to deliver conformal doses with effective gastrointestinal-OAR dose sparing despite using less modulation complexity. The dose of VMAT-HF was delivered with the same beam-on time with VMAT-FF but precise MLC leaf motions. The VMAT-HF can play a valuable role in reducing OAR toxicities associated with WPRT potentially.